PENINGKATAN PRESTASI BELAJAR MOTORIK LOMPAT TINGGI GAYA GUNTING MELALUI METODE POWER TRAINING - M. ANSHORI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
This research is a classroom action research related to improving motor learning achievement in high jump using scissor style through the power training method. The research method used is using 2 cycles, namely cycle 1 and cycle 2. In this cycle, it is translated into 2 meetings which begin with planning, action, observation, and reflection. The research subjects were students of class IX at MTsN Bakalan Rayung Jombang with a total of 30 students. The data collected in this study included observations, test results, and interviews. Based on the results of data analysis in cycle I, it can be seen that most of the students, as many as 22 students (73.33%), have not been able to do the scissor style high jump properly and perfectly because they are still below the minimum achievement of the Physical Education KKM, namely 75. Students' motor learning achievement is still low and based on initial observations showed an average value of 71.40, besides that there were no students who were able to achieve motor learning achievement. The scissor style high jump was very good (91-100). From the results of data analysis it can be seen that the average value of the practical test results was 77.80, the highest score was 88, and the lowest score was 72. Furthermore, based on data analysis in cycle II regarding the level of motor learning achievement Scissor style high jump, it turns out that no students have were able to achieve a very good level of motor learning achievement (91 - 100), 27 students or 90.00% were able to achieve a good level of motor learning achievement (75 - 90), 3 students or 10.00% achieved a moderate level of motor learning achievement ( 60 - 74), there were no students who achieved less motor learning achievement (40 - 59). So that from the presentation of the values obtained from the results of observations, tests, and interviews from the two cycles, success and improvement in learning achievement in scissor style high jump motor learning were achieved through the power training method. ABSTRAKPenelitian ini merupakan penelitian tindakan kelas terkait peningkatan prestasi belajar motorik lompat tinggi dengan gaya gunting melalui metode power training (latihan kekuatan). Metode penelitian yang digunakan adalah menggunakan 2 siklus, yaitu siklus 1 dan siklus 2. Pada siklus ini dijabarkan menjadi 2 kali pertemuan yang diawali dengan perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IX pada MTsN Bakalan Rayung Jombang dengan jumlah 30 siswa. Data yang dikumpulkan dalam penelitian ini meliputi dari hasil observasi, hasil tes, dan wawancara. Berdasarkan hasil analisis data pada siklus I dapat diketahui bahwa sebagian besar siswa sebanyak 22 siswa (73,33%) belum mampu melakukan Lompat tinggi gaya gunting dengan baik dan sempurna karena masih dibawah pencapaian minimal KKM Penjaskes yaitu 75. Prestasi belajar motorik siswa masih rendah dan berdasarkan observasi awal menunjukkan nilai rata-rata 71,40, disamping itu belum ada siswa yang mampu mencapai prestasi belajar motorik Lompat tinggi gaya gunting amat baik (91 – 100). Dari hasil analisis data dapat diketahui bahwa rata-rata nilai hasil tes praktek sebesar 77,80, nilai tertinggi 88, dan nilai terendah 72. Selanjutnya berdasarkan analisis data pada siklus II tentang tingkat prestasi belajar motorik Lompat tinggi gaya gunting, ternyata belum ada siswa yang mampu mencapai tingkat prestasi belajar motorik amat baik (91 - 100), 27 siswa atau 90,00% yang mampu mencapai tingkat prestasi belajar motorik baik (75 - 90), 3 siswa atau 10,00% yang mencapai tingkat prestasi belajar motorik cukup (60 - 74), tidak ada siswa yang mencapai prestasi belajar motorik kurang (40 - 59). Sehingga dari paparan nilai yang didapat dari hasil observasi, tes, maupun wawancara dari kedua siklus tersebut telah mencapai kesuksesan dan peningkatan dalam prestasi belajar motorik lompat tinggi gaya gunting melalui metode power training.